Applications of dispersed phase acoustics - Czyż, H.; Markowski, T. (Archives of Acoustics, 2006)
The problem of the influence of the acoustic field on dispersed phase in the fluid has beenstudied in connection with application of acoustic coagulation for precipitation of gases. Thissubject contains important aspects of the natural environment protection. This paper gives anoverview of the applications of dispersed phase acoustics, with particular emphasis on recentdevelopments, e.g. acoustic method of airport fog precipitation. This innovative technology isbased on the fact that water can be collected from fogs under the influence of acoustic waves.This work presents the new results of the analysis of the action of the acoustic field on thefogs.